Bio-clogging mitigation in the leachate collection system of municipal solid waste landfill using graphene oxide-coated geotextiles. (April 2021) - Wang, Qian; Ko, Jae Hac; Liu, Feng; Xiong, Wei; Wang, Xinwei; Xu, Qiyong
Abstract: In this study, graphene oxide (GO) was coated in geotextiles (GO-GT) to evaluate its potential for bio-clogging mitigation in the leachate collection system (LCS) of a landfill. Results showed that GO coating enhanced the surface hydrophilicity of geotextile. Bacterial experiments revealed that dead cells in the bio-clogging increased to 68.7% with GO-GT, compared to that in the GT (44.0%). After 136 days of operation, the GO-GT reduced the bio-clogging by decreasing the total amount of bacteria and the percentage of living bacteria. The total amount of extracellular polymeric substances in the GO-GT and GT was 22.8 ± 4.4 and 52.8 ± 4.8 mg/g of volatile suspended solids, respectively. Microbial analysis showed that Limnochordia and Symbiobacteriia were the most sensitive groups, with a decreased percentage in the GO-GT. Electrostatic repulsion and surface wrinkling were attributed to the attenuation effect on the GO-GT. These results imply the potential application of GO-coated geotextile for reducing bio-clogging in landfill LCS. Graphical abstract: Image 1 Highlights: The graphene oxide-coated geotextiles could mitigate bio-clogging in landfills. The bacteria were killed in graphene oxide coated geotextile. Proteins and polysaccharides contents were reduced in graphene oxide coated geotextile. The microbial diversity changed accordingly to the presence of graphene oxide.